Gold(I)/chiral brønsted acid catalyzed enantioselective hydroamination-hydroarylation of alkynes: effect of remote hydroxyl group in the reactivity and enantioselectivity - Shinde, Valmik S.; Mane, Manoj V.; Vanka, Kumar; Mallick, Arijit; Patil, Nitin T. (Chemistry - A European Journal, 2015)

Gold vs rhodium catalysis: tuning reactivity through catalyst control in the C-H alkynylation of isoquinolones - Shaikh, Aslam C.; Shinde, Dinesh R.; Patil, Nitin T. (Organic Letters, 2016)
A site-selective C-4/C-8 alkynylation of isoquinolones catalyzed by gold and rhodium complexes is reported. A broad range of synthetically useful functional groups (-F, -Cl, -Br, -CF3, -OMe, alkyl, etc.) were tolerated, providing an efficient and robust protocol for the synthesis either C-4- or C-8-alkynylated isoquinolones.

Gold(I)-catalyzed hydroaminaloxylation and petasis-ferrier rearrangement cascade of aminaloalkynes - Gade, Amol B.; Patil, Nitin T. (Organic Letters, 2016)
An efficient method has been developed to generate a diverse array of indolizidines and quinolizidines from readily available aminaloalkynes via a gold(I)-catalyzed hydroaminaloxylation and Petasis-Ferrier rearrangement cascade. The method enabled a formal synthesis of (+/-)-antofine.

Gold-catalyzed dehydrazinative C(sp)-S coupling reactions of arylsulfonyl hydrazides with ethynylbenziodoxolones for accessing alkynyl sulfones - Shinde, Popat S.; Patil, Nitin T. (European Journal of Organic Chemistry, 2017)
A gold(III)-catalyzed dehydrazinative coupling reaction between arylsulfonyl hydrazides and ethynylbenziodoxolone reagents was realized for the synthesis of alkynyl sulfones. The scope and versatility of the reaction were demonstrated by the efficient synthesis of 23 derivatives with diverse structural features.

Gold(I)-catalyzed cross-coupling reactions of aryldiazonium salts with organostannanes - Akram, Manjur O.; Shinde, Popat S.; Chintawar, Chetan C.; Patil, Nitin T. (Organic & Biomolecular Chemistry, 2018)
Gold(I)-catalyzed cross-coupling reactions of aryldiazonium salts with organostannanes are described. This redox neutral strategy offers an efficient approach to diverse biaryls, vinyl arenes and arylacetylenes. Monitoring the reaction with NMR and ESI-MS provided strong evidence for the in situ formation of Ph3PAuIR (R = aryl, vinyl and alkynyl) species which is crucial for the activation of aryldiazonium salts.

Gold-catalyzed 1,2-oxyalkynylation of N-Allenamides with ethylnylbenziodoxolones - Banerjee, Somsuvra; Senthilkumar, Beeran; Patil, Nitin T. (Organic Letters, 2019)
A gold-catalyzed 1,2-oxyalkynylation of N-allenamides with ethylnylbenziodoxolones (EBXs) has been achieved for the first time. The reaction, which follows a redox-neutral Au(I)/Au(III) catalytic pathway, was enabled in an attempt to exhaust the EBX reagents atom-economically by putting the nucleophilic carboxylate part of EBXs to appropriate use. This constitutes the first example for gold-catalyzed beta-alkynylation of N-allenamides to construct highly valuable 1,3-enynes. The potential of the sequence is further documented by some follow-up transformations.

Gold-catalyzed cycloisomerization of pyridine-bridged 1,8-Diynes: An expedient access to luminescent cycl[3.2.2]azines - Chintawar, Chetan C.; Mane, Manoj V.; Tathe, Akash G.; Biswas, Suprakash; Patil, Nitin T. (Organic Letters, 2019)
Gold-catalyzed diyne cycloisomerizations involving carbene/alkyne metathesis have been the focal point of attention for the past few years as it offers great potential to build complex polycyclic architectures. However, the design of novel cycloisomerizations has been mostly limited to 1,5/1,6-diynes and has remained very challenging to apply for higher 1,n-diynes. Herein, we disclose an unprecedented cycloisomerization of pyridine-bridged 1,8-diynes involving carbene/alkyne metathesis to access luminescent cycl[3.2.2]azines.

Gold(I)-catalyzed hydroxy group assisted C(sp(2))-H alkylation of enaminones with diazo compounds to access 3-alkyl chromones - Bagle, Pradip N.; Mane, Manoj V.; Sancheti, Shashank P.; Gade, Amol B.; Shaikh, Samir R.; Baik, Mu-Hyun; Patil, Nitin T. (Organic Letters, 2019)
A strategy for expedient synthesis of 3-substituted chromones from easily available o-hydroxyarylenaminones and diazo compounds has been developed. Carefully conducted experimental and computational studies led us to propose an uncommon mechanistic pathway involving the hydroxyl group assisted alkylation of enaminones with in situ generated gold carbenes.

Gold and hypervalent iodine(iii): liaisons over a decade for electrophilic functional group transfer reactions - Banerjee, Somsuvra; Bhoyare, Vivek W.; Patil, Nitin T. (Chemical Communications, 2020)
Over the last two decades, hypervalent iodine(iii) reagents have evolved from being `bonding curiosities' to mainstream reagents in organic synthesis, in particular, electrophilic functional group transfer reactions. In this context, gold catalysts have not only emerged as a unique toolbox to facilitate such reactions (especially alkynylations) but also opened new possibilities with their different modes of reactivities for other functional group transfer reactions (acetoxylations and arylations). This feature article critically summarizes hitherto all such Au-catalyzed electrophilic functional group transfer reactions with hypervalent iodine(iii) reagents, emphasizing their mechanistic aspects.

Gold-catalyzed alkynylative meyer-schuster rearrangement - Banerjee, Somsuvra; Ambegave, Shivhar B.; Mule, Ravindra D.; Senthilkumar, Beeran; Patil, Nitin T. (Organic Letters, 2020)
By applying the ``interplay'' mode, which consolidates two key reactivity modes of gold catalysis, namely pi-activation mode and cross-coupling mode, the first alkynylative Meyer-Schuster rearrangement is designed and successfully implemented. The current protocol gives straightforward access to enynones, a highly valuable building block, from easily available propargyl alcohol feedstocks. Control experiments suggest an Au(III) catalyst triggers the Meyer-Schuster rearrangement, whereas monitoring the reaction with ESI-HRMS provided strong evidence in favor of a key alkynylgold(III) intermediate which supports the proposed ``interplay'' scenario.